Release of TGF-β3 from Surface-Modified PCL Fiber Mats Triggers a Dose-Dependent Chondrogenic Differentiation of Human Mesenchymal Stromal Cells - Leonie Berten-Schunk; Yvonne Roger; Heike Bunjes; Andrea Hoffmann (MDPI AG, 2023)
The design of implants for tissue transitions remains a major scientific challenge. This is due to gradients in characteristics that need to be restored. The rotator cuff in the shoulder, with its direct osteo-tendinous junction (enthesis), is a prime example of such a transition. Our approach towards an optimized implant for entheses is based on electrospun fiber mats of poly(ε-caprolactone) (PCL) as biodegradable scaffold material, loaded with biologically active factors. Chitosan/tripolyphosphate (CS/TPP) nanoparticles were used to load transforming growth factor-β3 (TGF-β3) with increasing loading concentrations for the regeneration of the cartilage zone within direct entheses. Release experiments were performed, and the concentration of TGF-β3 in the release medium was determined by ELISA. Chondrogenic differentiation of human mesenchymal stromal cells (MSCs) was analyzed in the presence of released TGF-β3. The amount of released TGF-β3 increased with the use of higher loading concentrations. This correlated with larger cell pellets and an increase in chondrogenic marker genes (SOX9, COL2A1, COMP). These data were further supported by an increase in the glycosaminoglycan (GAG)-to-DNA ratio of the cell pellets. The results demonstrate an increase in the total release of TGF-β3 by loading higher concentrations to the implant, which led to the desired biological effect.